Investigating The Levels, Types, Causes and Coping Strategies of College Studentsâ€™ Foreign Language Writing Anxiety - Rini Anita; Zulhermindra Zulhermindra (Syntax Corporation, 2022)
The problem lied on foreign language writing anxiety suffered by the fourth semester students of English Education program of IAIN Batusangkar. They might get this for they were less familiar with argumentative course. Besides, there were some indicators that they had FLWA during teaching and learning process in the classroom like put off completing the assignment, as a result they prefer to be absent on the due date of submitted assignment, a fear of not getting a good idea to start the essay, or not creating a â€œgood enoughâ€ essay, and so forth. The research was aimed at analyzing studentsâ€™ level, types, causes and coping strategies to alleviate FLWA. The design of the research was mix method research. In conducting the research, the researchers used three kinds of questionnaires. The first questionnaire is used for analyzing studentsâ€™ level and type of FLWA, the second questionnaires is used for analyzing studentsâ€™ causes of FLWA, the third questionnaires is used for analyzing the strategies to alleviate FLWA suffered by the students. Then the researchers also used interview to clarify unclear information of the third questionnaires. The researchers analyzed the data quantitatively and qualitatively. At the end, the findings showed that the studentsâ€™ level of FLWA was in high level (62%) and moderate level (38%). The students also suffered somatic anxiety (mean score 23, 10), Cognitive anxiety (22,16), and Avoidance behavior (22, 29%). There 53 causes of FLWA had by students. There are several strategies used by students to alleviate FLWA like cognitive strategies, metacognitive strategies, social strategies, compensation strategies, and so forth.